CD30+ lymphomatoid papulosis in 16-year-old adolescent boy - Ruttala Sri Satya; Gandikota Raghurama Rao; Vijay Kumar Singh (Wolters Kluwer Medknow Publications, 2022)
Lymphomatoid papulosis (LYP) is a chronic CD30+ lymphoproliferative disorder that is rare among adults and even rarer in children. The disease is characterized by recurrent self-healing papulonodular eruptions that follow waxing and waning course over the years with an excellent prognosis. In adults, LYP is associated with an increased (10%-20%) risk of secondary lymphomas. The clinical features, course of the disease, and the risk of associated lymphoid malignancies in children are comparable with those of adults. We present a 16-year-old boy with 4-year history of asymptomatic, recurrent papulonodular lesions on the arms, right axilla, trunk, groin, and legs, healing with postinflammatory hyperpigmentation and atrophic scars. Histopathology and immunohistochemistry studies of these lesions are consistent with CD30+ LYP. We also discuss LYP in children with available literature.